Circulating miR-1 as a potential biomarker of doxorubicin-induced cardiotoxicity in breast cancer patients - Oliveira-Carvalho Vagner, Rigaud (Oncotarget, 2016)
Cardiotoxicity is associated with the chronic use of doxorubicin leading to cardiomyopathy and heart failure. Identification of cardiotoxicity-specific miRNA biomarkers could provide clinicians with a valuable prognostic tool. The aim of the study was to evaluate circulating levels of miRNAs in breast cancer patients receiving doxorubicin treatment and to correlate with cardiac function. This is an ancillary study from “Carvedilol Effect on Chemotherapy-induced Cardiotoxicity” (CECCY trial), which included 56 female patients (49.9±3.3 years of age) from the placebo arm. Enrolled patients were treated with doxorubicin followed by taxanes. cTnI, LVEF, and miRNAs were measured periodically. Circulating levels of miR-1, -133b, -146a, and -423-5p increased during the treatment whereas miR-208a and -208b were undetectable. cTnI increased from 6.6±0.3 to 46.7±5.5 pg/mL (p<0.001), while overall LVEF tended to decrease from 65.3±0.5 to 63.8±0.9 (p=0.053) over 12 months. Ten patients (17.9%) developed cardiotoxicity showing a decrease in LVEF from 67.2±1.0 to 58.8±2.7 (p=0.005). miR-1 was associated with changes in LVEF (r=-0.531, p<0.001). In a ROC curve analysis miR-1 showed an AUC greater than cTnI to discriminate between patients who did and did not develop cardiotoxicity (AUC = 0.851 and 0.544, p= 0.0016). Our data suggest that circulating miR-1 might be a potential new biomarker of doxorubicin-induced cardiotoxicity in breast cancer patients.